Private and community practice of dentistry (parallelism in management and planning process) - San Juan, Sofronio P.
Our undergraduate dental education is still disease and cure oriented. Individual dentists gear it to treatment of oral diseases of individual. The author is happy to note, however, that presently, there is a trend towards a multi-disciplinary or a team approach concept in patient management. And of course, an increasing awareness in community dentistry and prevention. This article will present the parallelism in the methods of private and community practice of dentistry as they relate to the functions of management and planning process... survey, analysis, program planning, program presentation, program implementation and evaluation. most autjors refere to the functions of management with the acronym, PIE (Planning, Implementation and Evaluation). In other words, the process of management of both our private patient and that of the community as a patient follows the same pattern.
Keywords: Dentistry -- Practice; Parallelism; Private practice; Community dentistry; Prevention; Functions of management; Planning process; Team approach; Multi-disciplinary.